Crank-Angle Resolved Flow Measurements in the Intake Duct of a Research Engine Using Novel and Fast Response Aerodynamic Probes - Großmann, Fabian; Mühlpfordt, Torsten; Rambacher, Patrick; Bikas, Georgios (Frontiers in Mechanical Engineering, 2021)
[23:03] bikasge Despite the public debate nowadays on the future of Internal Combustion Engines (ICE), which is impeding their development, one limitation towards further optimization of ICE in terms of fuel consumption and emissions can be seen in the current approach and more specifically in the transient engine operation and its control. The main drawbacks in the current approach source from: i) complex structure of mechanization including sensors and actuators, ii) low time resolution and accuracy of sensing (cost driven), iii) complex Electronic Control Unit (ECU)-software architecture associated with huge calibration effort and iv) in the last time, funded research due to unsecure business model of ICE is becoming less. To overcome these difficulties unexploited potential should be utilized. Some of this potential lies in cycle-by-cycle and cylinder-by-cylinder accurate fuel and air control, and in the development of physical based virtual sensors with high time resolution and accuracy. One of the main motivations for this study was to develop a measurement technique that enables crank-angle resolved air mass flow rate measurements during engine operation in a dynamometer test cell. The measurement principle is quite simple and is based on gauging the dynamic pressure in both the intake and exhaust duct at the closest possible positions to the valves. To fulfill these requirements aerodynamic probes have been developed and manufactured utilizing 3D printing. The probes have been integrated in special developed flanges, which correspond exactly to the shape of the air channels in the cylinder head of the engine. Hence, they can be mounted either in front of the valves at the intake or behind the valves at the exhaust duct.Results at different engine operating conditions have been obtained, analyzed and correlated to other sensors like air-flow meter. Those post-processed results can be further used to validate 1-D gas exchange models, or 3-D Computational Fluid Dynamics (CFD) port flow models. The ultimate scope of these measurements is to calibrate fast physical-based gas exchange models that can be directly used in the engine control framework on an embedded system.